2019
DOI: 10.1177/0267658319895551
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical aspect and L2 learners’ online processing of temporarily ambiguous sentences in English: A self-paced reading study with German, Dutch and French L2 learners

Abstract: The results of a self-paced reading study with advanced German, Dutch and French second language (L2) learners of English showed that their on-line comprehension of early closure (EC) sentences which are initially misanalysed by native English speakers (e.g., While John hunted the frightened rabbit escaped) was affected by whether or not, like English, their first language (L1) encodes aspect grammatically (French) or only via lexical means (German, Dutch). The English and the higher proficiency French partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…These research conclusions are in the line with other investigations (Klein & Manning, 2005;Bhandari, 2020;Roberts & Liszka, 2019) devoted to communicative competence. We agree with the scientists, we referred to above, that by developing communicative competence students become more confident in their class and everyday life activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These research conclusions are in the line with other investigations (Klein & Manning, 2005;Bhandari, 2020;Roberts & Liszka, 2019) devoted to communicative competence. We agree with the scientists, we referred to above, that by developing communicative competence students become more confident in their class and everyday life activities.…”
Section: Discussionsupporting
confidence: 93%
“…EFL learners should learn to communicate effectively in order to promote mutual respect, cooperation and problem-solving in an increasingly global and multicultural environment (Boyne, 2011;Jenkins, 2015;Li, 2016;Pring, 2012;Shohamy, 2011;Vettorel, 2016;Wierzbicka, 1985). The ability to communicate freely in a foreign language is one of the key competencies of an educated 21 st century person (Kasper & Omori, 2010;Roberts & Liszka, 2019). The key competency to be mastered by a student is the ability to speak a foreign language.…”
Section: Introductionmentioning
confidence: 99%
“…Their review, like ours, focused on the use of one particular elicitation procedure, self-paced reading, which has likewise been the subject of a number of debates concerning construct validity as well as what might constitute appropriate implementation and design (e.g. Keating and Jegerski, 2015;Roberts, 2016). Marsden et al's results indicated that the features of self-paced reading tasks vary widely.…”
Section: Methodological Transparency and Rigormentioning
confidence: 90%
“…This study concluded that, in L2 tense-aspect processing, only learners whose L1 has grammaticized aspect were sensitive to the tense aspect violations online; thus, the L2 tense-aspect processing is influenced by aspectual features in learners’ L1. Roberts and Liszka (2019) also found out the L1 effect on L2 processing and offline interpretations of aspectual distinction. The authors argued that whether a learner’s native language encodes progressive aspect via syntactic or only lexical means influences his/her interpretations of aspectual distinction.…”
Section: Literature Reviewmentioning
confidence: 86%